2021
DOI: 10.3389/fpsyt.2021.537309
|View full text |Cite
|
Sign up to set email alerts
|

Health Control Beliefs and Attitude Toward Treatment in Psychiatric and Non-Psychiatric Clinical Samples

Abstract: Although there is accumulating evidence on the potential influencing factors of medication adherence, the knowledge about patients' attitudes and beliefs toward treatment is only partly utilized in adherence-improving strategies. Several internal and external factors determining adherence have been described regarding many chronic somatic diseases but in recent research, insight on psychiatric patients has been exclusively lacking. As a result, there is a scarcity of effective adherence-improving interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The PHBQ-PT has been used in various studies to assess health beliefs and treatment adherence in patients with psychiatric disorders, including depression, bipolar disorder, and schizophrenia. [47][48][49][50][51] Overall, the PHBQ-PT is a useful tool for assessing health beliefs and treatment adherence in patients with psychiatric disorders, and can help healthcare providers tailor their approach to treatment to improve patient outcomes.…”
Section: The Patient's Health Belief Questionnaire On Psychiatric Tre...mentioning
confidence: 99%
“…The PHBQ-PT has been used in various studies to assess health beliefs and treatment adherence in patients with psychiatric disorders, including depression, bipolar disorder, and schizophrenia. [47][48][49][50][51] Overall, the PHBQ-PT is a useful tool for assessing health beliefs and treatment adherence in patients with psychiatric disorders, and can help healthcare providers tailor their approach to treatment to improve patient outcomes.…”
Section: The Patient's Health Belief Questionnaire On Psychiatric Tre...mentioning
confidence: 99%
“…It was also noted that individuals with a higher education level tend to be more skeptical about psychotropic medications [ 23 ]. Patients’ perceptions of health locus of control also influenced their view on the effects of medications [ 24 ]. Health locus of control was defined by the degree to which individuals believed that their mental state and body conditions were controlled by internal vs. external factors.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are confronted with the challenge of understanding and managing a complex disease process in their context. Without an understanding of their condition, they are unable to take necessary measures to maintain their health or make informed decisions about their well-being [ 28 , 29 ], which affects their adherence to recommended management strategies [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the understanding of the disease process by families and friends can have a significant impact on the patient's acceptance of pulmonary rehabilitation. There is also evidence that acceptance of pulmonary rehabilitation is affected by capability-related factors, such as patients' cognitive abilities, understanding of the disease, and their ability to access the programme [ 29 , 31 ]. We did not formally assess cognition but identified multiple practical barriers that reduced the ability to adhere to a pulmonary rehabilitation regime.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation